Developing instrumental, transversal and vertical skills through transformative methodologies - Claudio Melacarne (Formare, 2019)
The article deals with the concept of capability and soft skills and how these competencies are becoming central for instructors and educators in formal and informal adult education settings. The article starts questioning how higher education classrooms can become a space to promote employability using collaborative development and action inquiry.